2015
DOI: 10.1186/s12886-015-0013-3
|View full text |Cite
|
Sign up to set email alerts
|

Baseline traits of patients presenting at a low vision clinic in Shanghai, China

Abstract: BackgroundLow vision, along with cataract, trachoma, onchocerciasis, childhood blindness and refractive error, is one of the priorities in the global initiative, VISION 2020-The Right to Sight. The purpose of this study was to characterize the traits of patients presenting at a low vision clinic in China.MethodsA retrospective study was conducted of the records of 299 patients who visited the Low Vision Clinic of Eye and ENT Hospital Affiliated to Fudan University from January 2009 to May 2014. Reviewed parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 27 publications
3
13
1
1
Order By: Relevance
“…In 68% of children LVA could improve near visual acuity to N8 or better (P<0.01). Similar improvement in both near and distance visual acuity was reported by 12 For not purchasing LVA, cost was the major factor in BPL (n=5) children and cosmetic blemish was the major factor in APL children (n=6).…”
Section: Volume 29 Number 3 January-march 2019supporting
confidence: 69%
“…In 68% of children LVA could improve near visual acuity to N8 or better (P<0.01). Similar improvement in both near and distance visual acuity was reported by 12 For not purchasing LVA, cost was the major factor in BPL (n=5) children and cosmetic blemish was the major factor in APL children (n=6).…”
Section: Volume 29 Number 3 January-march 2019supporting
confidence: 69%
“…This result is in accordance with many studies in the developing countries where there is a predominance of younger age group attending low vision clinics. 22 , 24 , 26 , 27 Noticeably, there was low presentation of younger children in the study with the youngest age reported as 5 years. This is because the targeted clinic receives only children of school age (5 years and above), which suggests a limitation of low vision services in Jordan.…”
Section: Discussionmentioning
confidence: 67%
“…Affected patients, who bear mutations in one of a large (>200) set of causative genes (Daiger et al, ), progress typically to severe vision loss. Currently, RP lacks comprehensive treatment (Sacchetti et al, ) and is a leading cause of blindness in the young worldwide (Bunker et al, ; Gao et al, ; Haim, ). Elucidating cellular and molecular mechanisms common to various genetic etiologies of RP is of key importance in the search for treatments that can slow disease progression and vision loss (Sahel et al, ).…”
Section: Introductionmentioning
confidence: 99%